Measuring Socioeconomic Inequality in Health, Health Care and Health Financing by Means of Rank-Dependent Indices: A Recipe for Good Practice - Guido Erreygers; Tom Van Ourti (Tinbergen Institute, 2010)
The tools to be used and other choices to be made when measuring socioeconomic inequalities with rank-dependent inequality indices have recently been debated in this journal. This paper adds to this debate by stressing the importance of the measurement scale, by providing formal proofs of several issues in the debate, and by lifting the curtain on the confusing debate between adherents of absolute versus relative health differences. We end this paper with a matrix that provides guidelines on the usefulness of several rank-dependent inequality indices under varying circumstances
Keywords: D63; I10; 330; Health inequality; Socioeconomic inequality; Concentration Index; Gesundheit; Soziale Ungleichheit; Soziale Lage; Konzentrationsindex; Wohlfahrtstheorie